Non-coding RNAs at the intersection of epigenetics and cancer metabolism - Mangraviti, Nicolò; Castelli, Serena (Frontiers in Epigenetics and Epigenomics, 2025)
Cancer cells are primarily characterized by uncontrolled proliferation, which is closely linked to an increased energy demand. According to this, cancer cells preferentially utilize the glycolytic pathway for energy production. Metabolic regulation in cancer occurs at multiple levels, including post-translational modifications, which are rapid and energy-efficient, as they do not require enzyme degradation. In this context, non-coding RNA-mediated control plays a crucial role, as these small RNAs can directly modulate the mRNAs of key metabolic enzymes or induce epigenetic modulations, ultimately inducing alterations in cancer metabolism. In this mini-review, we summarize how non-coding RNAs (ncRNAs), including microRNAs, long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), modulate core metabolic pathways, including glycolysis, mitochondrial respiration, lipid metabolism, and amino acid biosynthesis, in cancer. We also highlight recent findings that uncover novel regulatory mechanisms and propose that ncRNAs serve as dynamic integrators of metabolic and oncogenic signals. Understanding these interactions may open new avenues for biomarker identification and ncRNAs-targeted therapies development.